2015
DOI: 10.1111/ppa.12381
|View full text |Cite
|
Sign up to set email alerts
|

Differential colonization patterns of Xylella fastidiosa infecting citrus genotypes

Abstract: Xylella fastidiosa is a phytopathogenic bacterium that causes disease in many different crops worldwide. In Brazil, X. fastidiosa subsp. pauca causes citrus variegated chlorosis (CVC), which is a disease responsible for economic losses in the citrus agribusiness. Variable host responses to bacterial colonization and disease development have been observed. This work studies the colonization processes of a pathogenic GFP-labelled X. fastidiosa citrus strain in sweet orange (susceptible) and tangor (resistant) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 35 publications
1
47
0
2
Order By: Relevance
“…60 The authors of this genomic analysis concluded that the high similarity might indicate identical metabolic functions shared by these two strains, which could likely use a common set of genes in plant colonization and pathogenesis, permitting convergence of functional genomic strategies. However, bacterial movement is slower in citrus plants, 61,62 suggesting that, in this case, cell adhesiveness may be 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 20 intrinsically different from X. fastidiosa Temecula 1. In fact, the adhesin function might be strongly related to the pathogen-host interaction, which determines adaptation mechanisms towards the host colonization.…”
mentioning
confidence: 99%
“…60 The authors of this genomic analysis concluded that the high similarity might indicate identical metabolic functions shared by these two strains, which could likely use a common set of genes in plant colonization and pathogenesis, permitting convergence of functional genomic strategies. However, bacterial movement is slower in citrus plants, 61,62 suggesting that, in this case, cell adhesiveness may be 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 20 intrinsically different from X. fastidiosa Temecula 1. In fact, the adhesin function might be strongly related to the pathogen-host interaction, which determines adaptation mechanisms towards the host colonization.…”
mentioning
confidence: 99%
“…In the susceptible sweet orange cv. It can locally multiply around the inoculation point but is unable to systemically invade the plant and to colonise tissues distant from the inoculation point (Niza et al, 2015). All sweet orange cultivars tested so far are susceptible, except Navelina ISA 315, which shows very low bacterial titre (Fadel et al, 2014).…”
Section: Background Informationmentioning
confidence: 99%
“…pauca (Coletta-Filho et al, 2007;Garcia et al, 2012;Niza et al, 2015). However, from the experimental evidence and the known variability in sweet orange-X.…”
Section: Conclusion On Citrus Spp As Hosts Of Xylella Fastidiosa Stmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterial strain used in our work has been modified to overexpress GFP using a genome‐integrated GFP gene . The autofluorescence spectral range of bacterial cells is usually rather large.…”
Section: Optical Measurementsmentioning
confidence: 99%